INTEGRASI HUKUM ISLAM DALAM SISTEM HUKUM INDONESIA: EVOLUSI DAN DINAMIKA SOSIAL-POLITIK - Abdullah, Zainuddin (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2024)
This study aims to analyze the evolution and integration of Islamic law in the Indonesian legal system, with a focus on the political dynamics that influence the legislative process. Islamic law in Indonesia has come a long way since the Dutch colonial era, where it served as a moral and legal foundation for Muslims. After independence, Islamic law began to be formalized in national legislation through various regulations such as the Marriage Law and the Compilation of Islamic Law. This integration of Islamic law was driven by the demands of the Muslim community to have clear legal guidance, especially in the field of family law. However, the process of Islamic law legislation is not free from socio-political influences. The role of Pancasila as the state ideology is key to maintaining a balance between Islamic law and democratic principles. Legal politics in Indonesia reflects the ongoing negotiation between religious principles and the needs of modern society. The Reformation era marked the strengthening of Islamic law in various sectors, including Islamic banking and halal product assurance, but also showed a decline in political support for Islamic parties. The results of this study suggest that Islamic law plays an important role in shaping the Indonesian legal system. Although challenges remain in integrating religious principles with democratic values, Islamic law continues to adapt to social and political changes in Indonesia